Different effects of air microembolism through patent foramen ovale in patients with migraine: A quantitative electroencephalogram case series - Ornello, Raffaele; Spezialetti, Matteo; Caponnetto, Valeria; Frattale, Ilaria; Grappasonni, Monica; Pistoia, Francesca; Placidi, Giuseppe; Sacco, Simona (Frontiers in Neurology, 2022)
Background Literature suggests an association between patent foramen ovale (PFO) and migraine, mostly migraine with aura (MA). Previous data suggest that air microembolism through PFO can lead to bioelectrical abnormalities detectable at electroencephalogram (EEG) in patients with MA, thus suggesting a pathophysiological mechanism for the MA-PFO association. However, those data lack replication. Methods Patients with MA or migraine without aura (MO) and large PFO underwent a 19-channel EEG recording before and after injection of air microbubbles. We compared EEG power before and after microbubble injection for each electrode location, for each frequency band (theta: 5–7 Hz; alpha: 8–12 Hz; beta: 13–30 Hz; lower gamma: 31–45 Hz), and for total global power (the average of EEG power at each location and frequency band). Results We included 10 patients, four with MA and six with MO; six patients had medium-to-high migraine frequency (four or more monthly migraine days), while four had low frequency (one monthly migraine day). EEG power changes after air microembolism varied across patients. Considering the overall group, total global EEG power did not change; however, EEG power in the higher frequency ranges (beta and lower gamma) increased in patients with MA. Conclusions We did not replicate the effects of air microembolism previously reported in patients with migraine. Aura status, migraine frequency, and medications might influence patients' response to microembolism. More refined EEG measurements are needed to clarify the dynamic role of PFO on migraine occurrence.